Balanced Scorecard: A Strategy for the Quality Improvement of Islamic Higher Education - Ilyasin, Mukhammad; Zamroni, Zamroni (Dinamika Ilmu, 2017)
The main issue in improving the quality of Islamic Higher Education is to increase the competence and professionalism of teachers and education personnel to achieve its vision and mission in the middle of the complexity of the demands of society and the changing times. so that the quality of education and governance of Islamic Religion clean and transparent with the principles of good governance is achieved as a matter of strategic policy development, the concept of the balanced scorecard as a strategic management system that is implemented by a world-class organization and even as a means of guiding and driving the change management process and the culture of the organization, in this case integrated in educational organization in order to create Islamic institutions of higher education quality. Through the balanced scorecard, which focuses on four perspectives, namely financial perspective, customer perspective, internal business perspective and learning and growth perspective is expected to create a system of organizing the Islamic Higher Education that upholds the values of trust, tafaqquh fi 'l-Din, professional, transparent, accountable and quality. Through balanced scorecard Similarly, Islamic higher education will be more qualified, marketable and globally competitive.